Ekspresi Keberagaman Online: Media Baru dan Dakwah - Asmar, Afidatul (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2020)
This paper explain how diversity expression of dakwah in new media. Today, media makes many preachers and madâ€™u use new media facilities, including internet media where content to Islam is packaged in stories of everyday life and given with funny things. this strategy attracts many interested people on both sides of the preacher and the mad'u themselves. Da'wah is the one of the activities aimed at inviting others in kindness, reminiscent of the end of the day, while new media is a tool used to invite others to better paths. In other developments the question arises regarding human imagination about God and the path of understanding spirituality experiencing setbacks or impoverishment in the digital age. Will the path of God's search for this generation of media cause visitors to the place of worship to recede, the preaching of the Scriptures is not heard, and the spirit of the religious community was down. Is the â€œnew media gedia generationâ€ aware or not â€œdeifyâ€ â€œvirtual Godâ€. This research uses a case study on the response of preachers and people related to the expression of diversity in using new media, so that how to interpret the message in the social media content Instagram, Facebook, Twitter and YouTube which is a unity of the internet world.Â Tulisan ini berupaya menjelaskan bagaimana dakwah dengan ekspresi keberagaman pada media baru saat ini. Dewasa ini media membuat banyak pendakwah maupun madâ€™u memanfaatkan fasilitas media baru, diantaranya media internet dimana konten-konten ke Islaman yang dikemas dengan santai dalam cerita kehidupan sehari-hari serta dibumbuhi hal-hal lucu. Strategi ini banyak menjaring peminat pada kedua sisi baik pendakwah maupun para madâ€™u itu sendiri. Dakwah adalah salah satu kegiatan yang bertujuan mengajak orang lain dalam kebaikan, mengingatkan terhadap hari akhir, sedangkan media baru adalah alat yang digunakan untuk mengajak orang lain kejalan yang lebih baik. Pada perkembangan lain muncul pertanyaan terkait imajinasi manusia tentang Tuhan dan jalan pemahaman spritualitas mengalami kemunduran atau pemiskinan di era digital. Apakah jalan pencarian Tuhan generasi media ini akan menyebabkan pengunjung tempat ibadah surut, pemberitaan Kitab Suci tidak didengar, dan spirit komunitas keagamaan tatap muka meredup. Apakah â€œgenerasi media baruâ€ ini sadar atau tidak mulai : â€œmenuhankanâ€ â€œTuhan-tuhan virtualâ€. Penelitian ini menggunakan studi kasus terhadap respon pendakwah dan umat terkait ekspresi keberagaman didalam menggunakan media baru, sehingga bagaimana memaknai pesan dakwah yang terkandung didalam konten-konten media sosial Instagram, facebook, twitter maupun youtube yang merupakan satu kesatuan dunia internet.